2024
DOI: 10.1038/s41586-024-07109-5
|View full text |Cite
|
Sign up to set email alerts
|

A concerted neuron–astrocyte program declines in ageing and schizophrenia

Emi Ling,
James Nemesh,
Melissa Goldman
et al.

Abstract: Human brains vary across people and over time; such variation is not yet understood in cellular terms. Here we describe a relationship between people’s cortical neurons and cortical astrocytes. We used single-nucleus RNA sequencing to analyse the prefrontal cortex of 191 human donors aged 22–97 years, including healthy individuals and people with schizophrenia. Latent-factor analysis of these data revealed that, in people whose cortical neurons more strongly expressed genes encoding synaptic components, cortic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 160 publications
0
12
0
Order By: Relevance
“…Notably, several studies have indicated a high prevalence of frailty among individuals diagnosed with schizophrenia, including those in younger age groups ( 39 , 40 ). Recent studies also have demonstrated strikingly similar patterns of gene activity in aging and schizophrenic patients, particularly in neurons and astrocytes in the prefrontal cortex ( 41 ). This indicates a potential association between frailty and schizophrenia.…”
Section: Discussionmentioning
confidence: 98%
“…Notably, several studies have indicated a high prevalence of frailty among individuals diagnosed with schizophrenia, including those in younger age groups ( 39 , 40 ). Recent studies also have demonstrated strikingly similar patterns of gene activity in aging and schizophrenic patients, particularly in neurons and astrocytes in the prefrontal cortex ( 41 ). This indicates a potential association between frailty and schizophrenia.…”
Section: Discussionmentioning
confidence: 98%
“…are gut microbes also known for interfering with the dopaminergic signaling, further linking cellular senescence to insufficient DA [31,32]. This is significant since both treated and untreated SCZ patients were found to exhibit body-wide premature cellular/neuronal aging, linking this condition to abnormal intestinal permeability [33,34]. Indeed, SCZ was associated with increased microbial migration into the host systemic circulation [35][36][37].…”
Section: Premature Cellular Senescence In Schizophreniamentioning
confidence: 99%
“…are gut microbes also known for interfering with dopaminergic signaling, further linking cellular senescence to insufficient DA [ 31 , 32 ]. This is significant since both treated and untreated SCZ patients were found to exhibit body-wide premature cellular/neuronal aging, linking this condition to abnormal intestinal permeability [ 33 , 34 ]. Indeed, SCZ has been associated with increased microbial migration into the host’s systemic circulation [ 35 , 36 , 37 ].…”
Section: Premature Cellular Senescence In Schizophreniamentioning
confidence: 99%